Hubungan Motivasi Perawat dengan Pelaksanaan Prinsip 12 Benar dalam Pemberian Obat di Ruang Rawat Inap RSU dr. H. Koesnadi Bondowoso (The Correlation between Nurses’ Motivation with the Implementation of 12 Principles of Right in Medicine Giving in Inpat - Retno Utami; Dodi Wijaya; Iis Rahmawati (Pustaka Kesehatan, 2015)
Nurse is the most appropriate medical staff to give medicine and vacate their time for the patients. In giving medicine, nurse also must concern on the given prescription must be appropriate, the exact qualification of dosis that is given and always applying 12 principles right away. This condition might cause the occurrence of interaction between the characteristic of a nurse that is her motivation and his work. The purpose of the research is to analyze the relation of nurse’s motivation and applied of 12 principles of right in giving medicine in inpatient wards of dr. H. Koesnadi hospital in Bondowoso. The design of this research that is used is observational analysis with cross sectional and sample approach used 51 correspondences. Data collection technique is sample probability with simply random sampling. The result of the data analysis used chi square test. The result show that P value 0.005 (0.005< α=0.05) means that there is relation between nurse’s motivation and the applies 12 principles of right in giving medicines having this research, hopefully for the institution of the hospital for increase even more the nurse’s motivation in working by giving reward and punishment to the nurses and give them special seminar related to 12 principles of right in giving medicines.   Keywords: nurse’s motivation, 12 principles of right in giving medicines, inpatient wards